2005
DOI: 10.1124/jpet.104.081711
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic- and Antidepressant-Like Profile of ATC0065 and ATC0175: Nonpeptidic and Orally Active Melanin-Concentrating Hormone Receptor 1 Antagonists

Abstract: Melanin-concentrating hormone (MCH) is a cyclic peptide produced in the lateral hypothalamus. It has been implicated in a number of physiological processes including feeding behavior, energy balance, and the regulation of emotional states. (1-10 mg/kg) significantly reduced immobility time in the forced swimming test in rats, indicating antidepressantlike effects. Both ATC0065 and ATC0175 significantly reversed swim stress-induced anxiety in the elevated plus-maze test in rats and stress-induced hyperthermia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
94
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 44 publications
10
94
0
Order By: Relevance
“…MCH injected directly into the lateral ventricle or the PVN stimulated the HPA axis (Jezova et al, 1992;Kennedy et al, 2003), and MCHR1 antagonists resembled known antidepressant and anxiolytic drugs (Borowsky et al, 2002;Chaki et al, 2005). Our data support these findings and expand on them by demonstrating a direct relationship between the anxiogenic effects of MCH and the reversal of these effects by selective MCHR1 blockade.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…MCH injected directly into the lateral ventricle or the PVN stimulated the HPA axis (Jezova et al, 1992;Kennedy et al, 2003), and MCHR1 antagonists resembled known antidepressant and anxiolytic drugs (Borowsky et al, 2002;Chaki et al, 2005). Our data support these findings and expand on them by demonstrating a direct relationship between the anxiogenic effects of MCH and the reversal of these effects by selective MCHR1 blockade.…”
Section: Discussionsupporting
confidence: 79%
“…infusion of MCH was reported to have either anxiogenic- (Gonzalez et al, 1996) or anxiolytic-like (Kela et al, 2003;Monzon and De Barioglio, 1999;Monzon et al, 2001) effects. Finally, novel MCHR1 antagonists blocked MCH-induced release of corticotrophin-releasing factor (Kennedy et al, 2003), and resembled known anxiolytics and antidepressants in animal models (Borowsky et al, 2002;Chaki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced anxiety-like behavior following acute treatment with SNAP-7941 (Borowsky et al, 2002) and ATC0065/0175 (Chaki et al, 2005) was observed in rats and mice using a variety of behavioral paradigms, much like the present study. Modulation of anxiety-like behavioral responses has also been observed following i.c.v.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, one explanation that must also be considered is that MCH signaling through its cognate receptor may act in a trophic manner to promote development of the serotonergic circuitry necessary for normal anxiety-like behaviors. However, in light of studies concluding that acute administration of a specific MCHR1 antagonist reduces anxiety-like behavior (Borowsky et al, 2002;Chaki et al, 2005), the trophic hypothesis of MCH signaling-induced effects on serotonergic transmission cannot solely explain the observed reduction in anxietylike behaviors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation